2009
DOI: 10.1111/j.1399-3054.2009.01278.x
|View full text |Cite
|
Sign up to set email alerts
|

Alternative oxidase involvement in Daucus carota somatic embryogenesis

Abstract: Plant alternative oxidase (AOX) is a mitochondrial inner membrane enzyme involved in alternative respiration. The critical importance of the enzyme during acclimation upon stress of plant cells is not fully understood and is still an issue of intensive research and discussion. Recently, a role of AOX was suggested for the ability of plant cells to change easily its fate upon stress. In order to get new insights about AOX involvement in cell reprogramming, quantitative real-time polymerase chain reaction (PCR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…Similar enhancement in AOX transcript accumulation upon MJ treatment was previously reported in Capsicum annuum (Fung et al, 2004) and in Lycopersicon esculentum (Fung et al, 2006). In the present study, the DcAOX2a and DcAOX1a genes were chosen for correlation studies with phenylpropanoid biosynthesis because of known involvement of these two AOX genes in the process of developmental and cell reprogramming Frederico et al, 2009). Recently, Campos et al (2009) showed developmental and tissue specific differential transcript accumulation of DcAOX2a and DcAOX1a in D. carota.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Similar enhancement in AOX transcript accumulation upon MJ treatment was previously reported in Capsicum annuum (Fung et al, 2004) and in Lycopersicon esculentum (Fung et al, 2006). In the present study, the DcAOX2a and DcAOX1a genes were chosen for correlation studies with phenylpropanoid biosynthesis because of known involvement of these two AOX genes in the process of developmental and cell reprogramming Frederico et al, 2009). Recently, Campos et al (2009) showed developmental and tissue specific differential transcript accumulation of DcAOX2a and DcAOX1a in D. carota.…”
Section: Discussionsupporting
confidence: 72%
“…SHAM (Aldrich, St. Louis, MO, USA) stock solution was prepared in dimethyl sulfoxide (Fluka BioChemika, St. Louis, MO, USA) essentially as described by Frederico et al (2009). From stock solution, different concentrations (0.1 mM, 0.2 mM, 0.4 mM, 0.5 mM and 0.8 mM) of SHAM were added to the liquid culture medium in conjugation with MJ (100 M).…”
Section: Experimental Design and Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to sustain the cell-vigour up-regulation of mitochondrial alternative oxidase ( AOX ) gene was observed enhancing the defense mechanism of the cell mainly through lowering down the reactive oxygen production (Maxwell et al 1999 ). Similarly, in carrot two AOX genes ( Dc AOX1a and Dc AOX2a) have been examined up-regulated during initiation of SE (Frederico et al 2009 ).Thus the AOX gene family has been identifi ed having crucial role in plant SE. Ca 2+ is one of the most important signalling molecules participating in many cellular pathways and transmitting different signals.…”
Section: +mentioning
confidence: 95%
“…The highest quality of the OES produced by the transgenic and the empty vector lines was 1.0. Somatic embryogenesis (SE), according to Frederico et al (2009), is the most prominent example of cell reprogramming, and has be interpreted as a stressinduced morphogenic response (Pasternak et al, 2002;Potters et al, 2007). The mitochondrion has been recognized to have strong effect on cell dedifferentiation (Amirsadeghi et al, 2007;Sheahan et al, 2005).…”
Section: Response Of Putative Transgenic Lines To Somatic Embryogenesismentioning
confidence: 99%